2016
DOI: 10.1007/s12282-016-0669-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of young age on local control after partial breast irradiation in Japanese patients with early stage breast cancer

Abstract: This is the first report of PBI efficacy in young patients in Asia. Although it is a nonrandomized retrospective chart review of a small cohort of patients with a relatively short follow-up period, PBI may be a better option than WBI following BCS in some young patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Overall, 36 studies published from 1989 to 2017 were used for the network meta-analysis . All trials were carried out in North America and Europe except one trial that was conducted in Japan (53). The reported mean or median age ranged from 42.4 to 70.8 years across the eligible studies.…”
Section: Characteristics Of the Identified Studiesmentioning
confidence: 99%
“…Overall, 36 studies published from 1989 to 2017 were used for the network meta-analysis . All trials were carried out in North America and Europe except one trial that was conducted in Japan (53). The reported mean or median age ranged from 42.4 to 70.8 years across the eligible studies.…”
Section: Characteristics Of the Identified Studiesmentioning
confidence: 99%
“…Although the current guidelines recommend optimal criteria for PBI, efforts to expand the PBI indications are still ongoing in many studies. A retrospective study on PBI with brachytherapy in 30 to 49 year-old patients found no significant difference in IBTR (97.6% vs. 95.5%, p = 0.70) and DFS (97.6% vs. 91.4%, p = 0.87) compared to WBI, suggesting the broader potential of PBI, even in younger patients [ 24 ]. Another retrospective study has suggested that PBI is a viable alternative to WBI in selected patients with invasive lobular histology [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…From Japan, Sato et al . compared the results of MIB with the outcomes of WBRT as adjuvant treatment following BCS, focusing particularly on patients’ age [ 34 ]. Of overall 184 patients, 99 received MIB and 85 WBRT, with patients’ age ranging from 30 to 49 years.…”
Section: Discussionmentioning
confidence: 99%
“…From Japan, Sato et al compared the results of MIB with the outcomes of WBRT as adjuvant treatment fol- lowing BCS, focusing particularly on patients' age [34].…”
Section: Discussionmentioning
confidence: 99%